2021
DOI: 10.1186/s12906-021-03464-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and anticancer activity of Falcaria vulgaris Bernh growing in Moghan plain, northwest of Iran

Abstract: Background Falcaria vulgaris Bernh among the most important member of Apiaceae family has been used for medical investigation in Iran and some regions in the world. This plant possesses a range of coumarin and flavonoids compounds that have many therapeutic properties such as gastrointestinal and liver diseases, skin ulcers, gastric ulcers, and intestinal inflammation. It has also been found that these compounds lead to cytotoxic effects. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Therefore, the findings of new antibiotics are an important point for the dissolving of the problems [ 2 ]. Recently, the researchers have found that a variety of natural sources, such as essential oil and extraction of herbs [ 24 , 28 , 29 ], environmental bacteria [ 23 ] and unhazardous fungi [ 30 ] can be used as novel antibiotics agents. Scientifics information on the safety and effectiveness of natural antibiotics’ remedies have shown that these agents have good anti-pathogenic activity with very low side effects [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings of new antibiotics are an important point for the dissolving of the problems [ 2 ]. Recently, the researchers have found that a variety of natural sources, such as essential oil and extraction of herbs [ 24 , 28 , 29 ], environmental bacteria [ 23 ] and unhazardous fungi [ 30 ] can be used as novel antibiotics agents. Scientifics information on the safety and effectiveness of natural antibiotics’ remedies have shown that these agents have good anti-pathogenic activity with very low side effects [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When apoptotic proteins are triggered, mitochondrial membranes lose their potential, and cancer cells' mitochondria become unable to function 55 . Flavonoids from ferns have also been demonstrated to have anticancer properties at very low doses in other investigations 56 . Polyphenols, as earlier stated, may alter the impact of proteins substances that may be employed to enhance cellular survival 57 .…”
Section: Flavonoidsmentioning
confidence: 97%
“…Medicinal plants have long been the most important source of treating various diseases. Today, cytotoxic secondary metabolites and their semi-synthetic derivatives have a special place in cancer therapies, therefore, the study of medicinal plants has been considered by researchers around the world [10,11]. Among the known medicinal plants, the genus Artemisia of the family Asteraceae has noteworthy compounds for their following effects: antioxidant activity [12], anti-inflammatory properties, antimalarial, antiviral, antibacterial, antifungal, and antitumor effects [13].…”
Section: Introductionmentioning
confidence: 99%